A Semi-Empirical Model of Winter Wheat Grain Protein Content (Global Journal of Science Frontier Research, 2022)
Winter wheat grain protein content GPC is an important criterion for assessing grain quality A timely and simple GPC model is urgently required for GPC prediction ahead of maturity The GPC model included regressional models of dry matter and N accumulation and translocation for anthesis and post-anthesis stages and incorporated both soil nitrogen N supply and meterological factors based on historical as well as current season data final GPC were calculated as the ratio of N accumulation to dry matter in grain at maturity This study conducted six field experiments during the 2003 2006 and 2008 2011 growing seasons to establish and validate the model A three-way factorial arrangement of N fertilization sowing date and cultivar was conducted using a split-plot design Critical growth parameters were determined by field measurements and historical seasonal meteorological data covering the growing period were collected The normalized root mean square error nRMSE which is defined as RMSE divided by the mean of the observed value multiplied by 100 was adopted to evaluate the model performance The major results were as follows 1 The prediction performance of dry matter DM and N accumulation NA and translocation during the pre-anthesis and post-anthesis periods were different it was poorer for the former and better for the latter However GPC prediction was not significantly affected by the intrinsic ratio-form of the GPC prediction 2 meteorological factors could capture the overall interannual trends of the corresponding dry matter and N sub-models in an acceptable manner 3 nRMSE and R2 of the semi-empirical GPC model Exp 4 and Exp 6 were 8 91 4 50 0 64 and 0 46 respectively and that of the simple linear model Exp 4 were13 3and 0 42 respectively The established semi-empirical model significantly improved the interannual and intra-annual prediction accuracy compared to the simple linear model
Keywords: triticum aestivum; grain nitrogen content; dry matter; meteorological factor